PELAKSANAAN PERATURAN DAERAH KOTA PEKANBARU NOMOR 13 TAHUN 2018 TENTANG PENEMPATAN TENAGA KERJA LOKAL DI KOTA PEKANBARU - WULAN SEPTIANI; Gusliana HB; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
This research was conducted at the Pekanbaru City ManpowerOffice. The problem in this research is how to implement RegionalRegulation Number 13 of 2018 concerning the Placement of LocalWorkers in Pekanbaru City, what are the inhibiting factors and what effortscan be made by the Manpower Office in the future. Data collectiontechniques in this study were conducted by interview method which wasconducted to research subjects by taking the Coordinator for DomesticPlacements and Foreign Workers as Key Informants, the types andsources of this research were primary data and secondary data. Thisresearch is in the form of qualitative analysis using analytical techniquesby describing and presenting theories that are in accordance with theexisting problems in the study This research consists of one variable, namely the implementation of Regional Regulation Number 13 of 2018concerning the Placement of Local Workers in Pekanbaru City by usingthree indicators. as a benchmark, namely mandatory reporting, Job SeekerRegistration and Supervision, research results obtained that theImplementation of Regional Regulation Number 13 of 2018 concerning thePlacement of Local Workers in Pekanbaru City has not been implementedproperly. There are still many companies that do not report any jobvacancies in their company to the Pekanbaru City Manpower Office. Thenin terms of providing guidance and supervision of job seekers, it has beenimplemented but has not been maximized, this is due to the lack of budget, lack of socialization guidance and limited resources. The power of theapparatus and the lack of Company Awareness are the inhibiting factorsfor the implementation of Regional Regulation Number 13 of 2018concerning the Placement of Local Workers in Pekanbaru City. For thisreason, it is hoped that the Pekanbaru City Manpower Office will alwayscarry out regular outreach developments to companies, carry outsanctions strictly in accordance with existing rules without exception andmaintain good cooperative relationships with companies in the city ofPekanbaru. Keywords :Implementation of regional regulation number 13 of 2018concerning the placement of local workers in the city of Pekanbaru